Multinationals stockpiling cash: Exploring a commodity boom - Erwin Hansen; Rodrigo Wagner (Inter-American Development Bank (IDB), 2015)
This paper explores how affiliates of multinational corporations save liquidity when facing a transitory cash-flow shock. For this a panel is first built of non-publicly traded copper mines in South America between 2001 and 2012, most of them set up as Foreign Direct Investment (FDI). This industry offers a peculiar advantage as a laboratory for social science when exploring cash-flow sensitivity: given time to build, investment decisions depend on the expectations of the long-run price of copper, while current cash flows depend only on the spot commodity's price. Although a robust effect of cash flow on current capital expenditures is not found, a much clearer picture is observed of the effects of transitory earnings on cash stockpiling: out of every extra dollar in cash, between 20 and 50 cents end up as extra cash holdings, especially among the most financially constrained firms. This was salient in the aggregate, since average cash holdings tripled as a share of assets during the commodity boom. The findings support financial theories remarking the salience of cash as a buffer stock for liquidity of financially constrained firms. Although the reinvestment of multinationals' earning is considered Foreign Direct Investment in the Balance of Payments, at least in the short run, a significant fraction of it does not constitute new investment in the National Accounts, since it remains among current rather than fixed assets.
hdl:11319/7006
Keywords: F23; F32; G31; G32; 330; Multinationals; Cash Holdings; Investment; Current Account Deficits